Preferensi Kepemilikan Rumah Bagi Masyarakat Berpenghasilan Rendah (Studi Kasus: Kota Payakumbuh) - Rika Fitriani; Werry Darta Taifur; Delfia Tanjung Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The functions of house not only as a residence, but also as an asset, investment, identity and a reflection of the preference of its inhabitants. Housing ownership for low-income people is something that is not easy, it needs support from the government through various housing supply and development programs. The government needs to pay attention to housing ownership preferences for low-income people in an effort to meet this housing need. This study aims to identify housing ownership preferences for low-income people who take the study area in Payakumbuh City. These preferences were identified using conjoint analysis by looking at four factors, namely the type of housing provision, financing scheme, price and location. The results showed that in general 250 respondent households chose the informal type of housing provision, namely building houses independently, the financing that was considered more considered was non-formal financing by making loans to family/friends, savings or by selling assets. The price of the selected house is under Rp. 100,000,000, - with a location on the outskirts of the city. The price factor is the most important factor in assessing or buying a house (41.467%), followed by the financing scheme factor (22.089%) then the location factor of the house (18.908%) and the type of house (14.736%). The correlation value with the Person's r method is 0.985 and with the Kendall's Tau method of 0.929 indicating that the respondent's preference is acceptable to describe the preference for home ownership with a small significant value of 0.05.